Research on the Impact of Long Term Care Insurance on Family Medical Expenditure: Empirical Evidence Based on CHARLS Data from 2011 to 2020 - Yang, Churui; Li, Rongxin; Zheng, Xunwen (Asia Pacific Economic and Management Review, 2026)
In recent years, the long-term care insurance system has played an important role in the social security system under the background of population aging. Different from previous studies that focused on the improvement effect of policies on the health status of the elderly, the evaluation of policy effects, and the limitations of data lag, this study adopts the latest CHARLS data from 2011 to 2020 and uses a difference in differences model to explore the impact of long-term care insurance policies on family medical expenditures, and deeply analyzes the mediating and moderating effects. Research has found that long-term care insurance can significantly reduce household medical expenses; Mechanism analysis shows that this policy improves the physical health status of disabled elderly people by providing professional nursing services, thereby achieving a decrease in family medical expenses; The number of children has a negative moderating effect on the effectiveness of policies; Heterogeneity analysis shows that long-term care insurance has a more prominent effect on reducing medical expenses for families of chronic disease patients and highly educated families. Based on the above conclusions, it is recommended to adopt a gradual promotion strategy, gradually expand the coverage and guarantee objects of the pilot program, develop personalized service plans based on differences in disability level, economic status, etc., strengthen the professional training of nursing talents, and establish a multidimensional evaluation mechanism to regularly monitor the effectiveness of policy implementation and dynamically adjust the implementation plan.